Review of current therapy of pancreatic pseudocysts - Guenther, L.; Hardt, P. D.; Collet, P. (Zeitschrift für Gastroenterologie, 2015)
Background and Aims: Therapeutic interventions for complicated pancreatitis, especially in pseudocysts and walled-off necroses as a sequel of necrotizing pancreatitis, have a long history. Originally a stronghold of classical surgery and radiology, in the last two decades this was increasingly supplemented by endoscopy, often with adjuvant percutaneous drainage, mostly reducing open surgery to a salvage intervention in case of failure and complication. This study aims to evaluate and compare the current therapeutic options for pancreatic fluid collections, especially pseudocysts.Methods: Systematic literature search via MedLine and Pubmed was performed with comprehensive tabulations of original publications of the endoscopic, surgical and percutaneous therapeutic interventions in pancreatic pseudocysts and WON in the last 27 years. Only studies including more than 10 cases were further analysed. The results with regard to complications, outcome, recurrence and mortality were analysed for each approach, the risk of bias was assessed and a conclusive statement was made.Results: The initial literature search identified 46 studies. 12 studies had to be excluded because the number of individuals included was too low. 34 endoscopic, 8 surgical and 8 percutaneous studies were further analysed, leading to a number of 2485 patients in this review. The short-term clinical success was 85 % for the endoscopic approach, 83 % for surgery and 67 % for the percutaneous intervention. The complication rates were 16 %, 45 % and 34 % for endoscopic, surgical and percutaneous therapy, respectively. Typical complications were hemorrhage, infection, perforation and, especially in the percutaneous approach, pancreatocutaneous fistulisation.Conclusion: According to the high success and low complication rates the endoscopic intervention appears as the most efficient method. But each method has its own indications, restrictions and therefore patient groups. Therefore it is reasonable to consider all the available methods in a productive interdisciplinary manner for the ultimate benefit of the patient in the future.
Keywords: Pankreaspseudozysten; walled-off Nekrosen; endoskopische Drainage; chirurgische Drainage; Pankreatitis; perkutane Drainage